2018
DOI: 10.3846/bme.2018.66
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Capital Development on Productivity Growth in Eu Member States

Abstract: Abstract. In this research, we investigate the impact of human capital on labour productivity in European Union member states using panel data analysis. Results of the paper are estimated using the Pooled ordinary least squares (OLS) and Fixed effects model (FEM). The results show that human capital is positively significant in improving the growth of labour productivity in the EU. Our estimates also suggest that the impact occurs after three times lags in case of education expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Health is one of the components of HC that are prerequisites for economic development ( 46 ) quality of health is substantially essential and positive for productivity and economic progress ( 47 ) demonstrated in the findings that improvement in health expenditures significantly enhances the HC of the country ( 48 ) investigated HC in improving substantial impact on productivity and growth ( 49 ) observed that HC directly or indirectly affects the economic growth of the country ( 50 ) also examined the association between HC, economic growth, and health expenditures in the case of developing economies. The results depicted that health expenses and economic growth are substantially associated with HC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Health is one of the components of HC that are prerequisites for economic development ( 46 ) quality of health is substantially essential and positive for productivity and economic progress ( 47 ) demonstrated in the findings that improvement in health expenditures significantly enhances the HC of the country ( 48 ) investigated HC in improving substantial impact on productivity and growth ( 49 ) observed that HC directly or indirectly affects the economic growth of the country ( 50 ) also examined the association between HC, economic growth, and health expenditures in the case of developing economies. The results depicted that health expenses and economic growth are substantially associated with HC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The direct relationship between investment in employee training and experience also investment in employee health, which are measured at macro level by public and private investment in the education system and healthcare system, as well as private training costs, generates increasing labor productivity. Figure (2) presents channels of human capital impact on labor productivity [18].…”
Section: Human Capital Development On Labor Productivitymentioning
confidence: 99%
“…A starting point for further considerations presented in this paper is the assumption about the existence of a close relationship between knowledge and innovation. The dissemination of knowledge generates further innovations (Mačiulytė-Šniukienė & Matuzevičiūtė, 2018;Roszko-Wójtowicz & Białek, 2017;Johansson, 2014;Niklewicz-Pijaczyńska & Wachowska, 2012). The justification for this state of affairs can be found in the following two factors: the process of globalisation of economies (Lu, Tsang, & Peng, 2008;Veugelers, 2010) and fast technological changes (Santos, Doz, & Williamson, 2004;Peng, 2006;Madsen, 2008;Bogliacino, Piva, & Vivarelli, 2012;Feldmann, 2013).…”
Section: Knowledge Economy Skills and Innovationmentioning
confidence: 99%